Frailty, multimorbidity and polypharmacy: exploratory analyses of the effects of empagliflozin from the EMPA-KIDNEY trial - Mayne, KM; Sardell, R; Staplin, N; Judge, P; Zhu, D; Sammons, E; Wanner, C; Emberson, J; Preiss, D; Landray, M; Baigent, C; Haynes, R; et al. (American Society of Nephrology, 2024)
Background: Sodium-glucose co-transporter-2 (SGLT2) inhibitors are recommended treatment for adults with chronic kidney disease (CKD), but uncertainty exists regarding their use in patients with frailty and/or multimorbidity, among whom polypharmacy is common. We derived a multivariable logistic regression model to predict hospitalization (reflecting frailty) and assessed empagliflozin’s risk-benefit profile in a post-hoc analysis of the double-blind, placebocontrolled EMPA-KIDNEY trial. Methods: The EMPA-KIDNEY trial randomized 6609 patients with CKD (estimated glomerular filtration rate [eGFR] ≥20<45 mL/min/1.73m2 , or ≥45<90 mL/min/1.73m2 with urinary albumin-to-creatinine ratio ≥200 mg/g) to receive either empagliflozin 10 mg daily or matching placebo and followed for two years (median). Additional characteristics analysed in subgroups were multimorbidity, polypharmacy and health-related quality of life (HRQoL) at baseline. Cox regression analyses were performed with subgroups defined by approximate thirds of each variable. Results: The strongest predictors of hospitalization were N-terminal prohormone of brain natriuretic peptide, poor mobility and diabetes; then eGFR and other comorbidities. Empagliflozin was generally well-tolerated independent of predicted risk of hospitalization. In relative terms, allocation to empagliflozin reduced the risk of the primary outcome of kidney disease progression or cardiovascular death by 28% (hazard ratio [HR] 0.72, 95% confidence interval [CI] 0.64-0.82); and all-cause hospitalization by 14% (HR 0.86, 95% CI 0.78-0.95); with broadly consistent effects across subgroups of predicted risk of hospitalization, multimorbidity, polypharmacy or HRQoL. In absolute terms, the estimated benefits of empagliflozin were greater in those at highest predicted risk of hospitalization (reflecting frailty) and outweighed potential serious harms. Conclusions: These findings support the use of SGLT2 inhibitors in CKD, irrespective of frailty, multimorbidity or polypharmacy.